Heterogeneous brain region-specific responses to astrocytic mitochondrial DNA damage in mice - Daniela A. Ayala; Anthony Matarazzo; Bonnie L. Seaberg; Misha Patel; Eliana Tijerina; Camryn Matthews; Gabriel Bizi; Ashton Brown; Alan Ta; Mendell Rimer; Rahul Srinivasan (Scientific Reports, 2024)
Abstract Astrocytes display context-specific diversity in their functions and respond to noxious stimuli between brain regions. Astrocytic mitochondria have emerged as key players in governing astrocytic functional heterogeneity, given their ability to dynamically adapt their morphology to regional demands on ATP generation and Ca2+ buffering functions. Although there is reciprocal regulation between mitochondrial dynamics and mitochondrial Ca2+ signaling in astrocytes, the extent of this regulation in astrocytes from different brain regions remains unexplored. Brain-wide, experimentally induced mitochondrial DNA (mtDNA) loss in astrocytes showed that mtDNA integrity is critical for astrocyte function, however, possible diverse responses to this noxious stimulus between brain areas were not reported in these experiments. To selectively damage mtDNA in astrocytes in a brain-region-specific manner, we developed a novel adeno-associated virus (AAV)-based tool, Mito-PstI expressing the restriction enzyme PstI, specifically in astrocytic mitochondria. Here, we applied Mito-PstI to two brain regions, the dorsolateral striatum and dentate gyrus, and we show that Mito-PstI induces astrocytic mtDNA loss in vivo, but with remarkable brain-region-dependent differences on mitochondrial dynamics, Ca2+ fluxes, and astrocytic and microglial reactivity. Thus, AAV-Mito-PstI is a novel tool to explore the relationship between astrocytic mitochondrial network dynamics and astrocytic mitochondrial Ca2+ signaling in a brain-region-selective manner.